Refiguring media: Tee shirts as a site of audience engagement with superheroes. Issue 5 (19th October 2016) - Gordon, Ian
ABSTRACT: In the last 20 years or so, new forms of media have resulted in new forms of engagement with media in general. The production and distribution of older forms of media have also undergone a transformation. Sales of the superhero genre of comic books have waned considerably even as advances in computer-generated imagery (CGI) have helped carry the spectacular imaginative events from their worlds to the screen. In this environment tee shirts have become an important medium through which audiences engage with superheroes. This article offers a historical account of that process.